Artificial Intelligence Based Study Association between p53 Gene Polymorphism and Endometriosis: A Systematic Review and Meta-analysis. (18th November 2022) - Ma, Xia; Jin, Xiaoxiao; Shao, Xiujuan; Hu, Wanjing; Jin, Haihong; Wang, Yiqun
Abstract : Background . The P53 gene is critical to the onset and progression of cancers. Currently, relevant study findings indicate that the p53 gene may have a strong association with the risk of endometriosis, but these findings have not been united. To gather more statistically meaningful clinical data, we used meta-analysis to examine the relationship between the rs1042522 single nucleotide polymorphism of the tumor suppressor gene p53 and the incidence of endometriosis. Methods . Through a comprehensive literature survey of PubMed, MEDLINE, EMBASE, Springer, and Web of Science literature databases, we obtained a clinical control case study on the relationship between p53 gene polymorphism and the prevalence of female endometriosis and finally traced the relevant references included. The quality of the literature included in this study was evaluated, and Revman5.3 was used to complete the meta-analysis. Results . This research includes eight publications. The total number of cases in the study group was 1551, whereas the total number of cases in the control group was 1440. The findings of the sensitivity analyses of each omitted piece of the literature revealed no significant difference. The results of the meta-analysis showed that there were significant differences in the GG gene frequency (OR = 0.56, 95%CI (0.38, 0.92), P = 0.003), allele G (OR = 2.46, 95%CI (1.41, 4.29), P = 0.002), and allele C (OR = 0.62, 95%CI (0.46, 0.84), P = 0.002) between the study group and the control group (P < 0.01), but there was no significant difference in the GC gene frequency (OR = 1.17, 95%CI (1.01, 1.36), P = 0.03), and the CC gene frequency (OR = 1.25, 95%CI (0.85, 1.82), P = 0.26) (P > 0.01). Conclusion . Our study results show that there is a significant correlation between the single nucleotide of the p53 gene and the incidence rate of female endometriosis, in which the decrease of the GG gene frequency and the increase of allele C are likely to increase the risk of such diseases.